Foreign direct investment and international business cycle comovement - W. Jos Jansen; Ad C.J. Stokman (European Central Bank (ECB), 2004)
This paper investigates the relationship between bilateral FDI positions and cross-country business cycle correlations in the period 1982–2001. We find that countries that have comparatively intensive FDI relations also have more synchronized business cycles during 1995–2001. Before 1995, we also find a positive association between FDI linkages and output comovement, but this may partly reflect the effects of trade relations. Moreover, more intensive FDI links are also associated with a greater vulnerability to lagged output spillovers from abroad, whereas trade links are not. Policy implications of our research are (1) that there is an underlying tendency for business cycles to exhibit greater comovement in the future, and (2) that policy makers need to incorporate the FDI linkage among economies in their models and analytical framework for policy analysis.
Keywords: E32; F21; J23; J31; 330; business cycle synchronization; Foreign Direct Investment; international linkages; spillovers